Teaching Listening at Upper-Secondary School - Kleprlík, Filip (Univerzita Pardubice, 2023)
This bachelor thesis deals with textbook evaluation from the perspective of teaching and learning strategies and techniques with a focus on listening. The theoretical part defines listening, sets listening in the context of other language skills and then introduces learning and teaching strategies and techniques. The second part of the theoretical part focuses on the textbook and its evaluation. The last chapter of the theoretical part deals with the evaluation of listening in the textbook. The aim of the practical part is to evaluate listening lesson in the textbook from the perspective of teaching and learning strategies and techniques.
Výuka poslechových dovedností v anglickém jazyce na středních školách
Keywords: poslechové strategie; učební strategie; učebnice; hodnocení; poslech; listening strategies; learning strategies; textbook; evaluation; listening